Students’ Motivation in Learning English at The Sixth Semester of Mathematics Education Program - Tantri Widiarti; Nurhaeda Gailea; Dhafid Wahyu Utomo (LPPM Universitas Bina Sarana Informatika, 2022)
This study intended to figure out the level and the dominant motivation in learning English for sixth-semester students majoring in the Mathematics Education Program of Sultan Ageng Tirtayasa University. This was viewed from three dimensions (Ideal L2 Self, Ought-to L2 Self, and L2 Learning Experience) of the L2 Motivational Self System framework of Dörnyei (2005, 2009). A quantitative research approach was employed through a survey study design to achieve the aim of the study. A total of 27 close-ended questionnaire items with a 5-point Likert Scale was administered to 79 participants. The main findings revealed that the motivation level of students held a moderate rate ( 3.53, SD = .870). Further description, 70% of students had a moderate level, and 30% reached a high level. Additionally, it found that the students were dominantly motivated by the L2 Learning Experience (= 3.67, SD = .756). It indicated that the motivation came from learning experiences and situations around students. While the Ideal L2 Self (= 3.63, SD = .878) was ranked in the second position, and Ought-to L2 Self (= 3.29, SD = .977) followed in the third position. Based on the research findings, some implications were recommended to be employed by EFL lecturers in enhancing students’ motivation, along with some directions for future researches in the area of motivational studies.